The role of species charisma in biological invasions. Issue 6 (6th April 2020) - Jarić, Ivan; Courchamp, Franck; Correia, Ricardo A; Crowley, Sarah L; Essl, Franz; Fischer, Anke; González‐Moreno, Pablo; Kalinkat, Gregor; Lambin, Xavier; Lenzner, Bernd; Meinard, Yves; Mill, Aileen; et al.
Abstract : Commonly used in the literature to refer to the "attractiveness", "appeal", or "beauty" of a species, charisma can be defined as a set of characteristics – and the perception thereof – that affect people's attitudes and behaviors toward a species. It is a highly relevant concept for invasion science, with implications across all stages of the invasion process. However, the concept of invasive alien species (IAS) charisma has not yet been systematically investigated. We discuss this concept in detail, provide a set of recommendations for further research, and highlight management implications. We review how charisma affects the processes associated with biological invasions and IAS management, including species introductions and spread, media portrayals, public perceptions of species management, research attention, and active public involvement in research and management. Explicit consideration of IAS charisma is critical for understanding the factors that shape people's attitudes toward particular species, planning management measures and strategies, and implementing a combination of education programs, awareness raising, and public involvement campaigns.